The Role of Stokes Drift in the Dispersal of North Atlantic Surface Marine Debris - Bosi, Sofia; Broström, Göran; Roquet, Fabien (Frontiers in Marine Science, 2021)
Understanding the physical mechanisms behind the transport and accumulation of floating objects in the ocean is crucial to efficiently tackle the issue of marine pollution. The main sinks of marine plastic are the coast and the bottom sediment. This study focuses on the former, investigating the timescales of dispersal from the ocean surface and onto coastal accumulation areas through a process called “beaching.” Previous studies found that the Stokes drift can reach the same magnitude as the Eulerian current speed and that it has a long-term effect on the trajectories of floating objects. Two particle tracking models (PTMs) are carried out and then compared, one with and one without Stokes drift, named PTM-SD and PTM-REF, respectively. Eulerian velocity and Stokes drift data from global reanalysis datasets are used for particle advection. Particles in the PTM-SD model are found to beach at a yearly rate that is double the rate observed in PTM-REF. The main coastal attractors are consistent with the direction of large-scale atmospheric circulation (Westerlies and Trade Winds). After 12 years (at the end of the run), the amount of beached particles is 20% larger in PTM-SD than in PTM-REF. Long-term predictions carried out with the aid of adjacency matrices found that after 100 years all particles have beached in PTM-SD, while 8% of the all seeded particles are still floating in PTM-REF. The results confirm the need to accurately represent the Stokes drift in particle models attempting to predict the behaviour of marine debris, in order to avoid overestimation of its residence time in the ocean and effectively guide policies toward prevention and removal.